A retail price index including the shadow price of owner occupied housing - Laura Blow; Lars Nesheim (Centre for Microdata Methods and Practice (cemmap), 2009)
How do house price changes affect the cost of living? The retail price index in the UK does not directly incorporate house price changes. Instead it uses mortgage interest to capture the cost of owning a home. This is a useful method from many perspectives. However, from a consumer welfare perspective, while mortgage interest does capture the cost of a particular service, it does not capture the cost of housing services. The shadow price of housing captures the welfare cost to a household of changes in housing prices. In this paper we create a new shadow price index using RPI data and the shadow price of housing and investigate how replacing the mortgage interest with the shadow price of housing affects measures of the cost of living.
Keywords: C43; E31; R21; 330; housing; retail price index; shadow price; user cost; Einzelhandelspreisindex; Wohneigentum; Wohnkosten; Opportunitätskosten; Großbritannien